ANALISIS PENGARUH JUMLAH PENDUDUK, INVESTASI, PENGELUARAN PERKAPITA TERHADAP PERTUMBUHAN EKONOMI - Sanjani, Muhammad Rafi'i; Sari, Indah Fitriana (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2025)
The influence of population, investment, and per capita expenditure on economic growth in West Nusa Tenggara (Nusa Tenggara Barat) from 2019 to 2023. This study is motivated by the need to understand the dynamics of economic development in a region characterized by its unique demographic and economic conditions. This study aims to provide valuable insights for future research and serve as a reference for policymakers to develop effective economic strategies. This study uses a quantitative approach, data is collected through documentation and literature studies from reliable sources, including the Central Statistics Agency. The analysis uses panel data regression to assess the relationship between variables. The results of the study indicate that when analyzed simultaneously, population, investment, and per capita expenditure do not significantly affect economic growth in West Nusa Tenggara. Specifically, statistical tests show that the population variable has a p-value of 0.95, indicating no significant impact on economic growth. Likewise, investment shows a p-value of 0.956, and per capita expenditure has a t-count value lower than the t table, indicating a lack of influence on economic growth. These results imply that current consumption and investment patterns in West Nusa Tenggara may not be conducive to increasing local economic productivity. The conclusion of this study is that population, investment, and per capita expenditure do not have a significant effect on economic growth in West Nusa Tenggara, either simultaneously or partially.